1994
DOI: 10.1111/j.1432-1033.1994.tb18774.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteins under pressure

Abstract: Oceans not only cover the major part of the earth's surface but also reach into depths exceeding the height of the Mt Everest. They are populated down to the deepest levels (=11800 m), which means that a significant proportion of the global biosphere is exposed to pressures of up to 120 MPa. Although this fact has been known for more than a century, the ecology of the 'abyss' is still in its infancy. Only recently, barophilic adaptation, i.e. the requirement of elevated pressure for viability, has been firmly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
399
0
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(415 citation statements)
references
References 128 publications
9
399
0
7
Order By: Relevance
“…Experimental techniques such as optical spectroscopy, Raman scattering, and NMR have been used to observe pressure effects on proteins (Weber & Drickamer, 1983;Frauenfelder et al, 1990;Jaenicke, 1991;Silva & Weber, 1993;Gross & Jaenicke, 1994 . The pressure denaturation of monomeric proteins, the dissociation of oligomers, and the effects of pressure on macromolecular assemblages have provided insights into the microscopic mechanism of protein folding and the role of solvent in this process (Zipp & Kauzmann, 1973;Li et al, 1976;Chryssomallis et al, 1981;Weber & Drickamer, 1983;Silva et al, 1986;Silva & Weber, 1993;Weber, 1993;Dufour et al, 1994;Peng et al, 1994;Schulte et al, 1995;Silva et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental techniques such as optical spectroscopy, Raman scattering, and NMR have been used to observe pressure effects on proteins (Weber & Drickamer, 1983;Frauenfelder et al, 1990;Jaenicke, 1991;Silva & Weber, 1993;Gross & Jaenicke, 1994 . The pressure denaturation of monomeric proteins, the dissociation of oligomers, and the effects of pressure on macromolecular assemblages have provided insights into the microscopic mechanism of protein folding and the role of solvent in this process (Zipp & Kauzmann, 1973;Li et al, 1976;Chryssomallis et al, 1981;Weber & Drickamer, 1983;Silva et al, 1986;Silva & Weber, 1993;Weber, 1993;Dufour et al, 1994;Peng et al, 1994;Schulte et al, 1995;Silva et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Life, including macrofauna, is found at all depths, an observation that belies the extent to which pressure can affect biological function. Increasing pressure affects fundamental cellular processes such as enzyme activity, action potential propagation, synaptic transmission, and overall protein function and regulation (Campenot, 1975;Gross and Jaenicke, 1994;Somero, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic amino acid changes that increase protein stability are also documented in several marine fish. A number of cytosolic proteins have been investigated in both shallow and deep living species (Stefanni et al, 2014), including lactate dehydrogenase (Brindley et al, 2008;Campenot, 1975;Gross and Jaenicke, 1994;Hennessey and Siebenaller, 1987;Somero, 1992), -actin (Morita, 2010;Swezey and Somero, 1982;Wakai et al, 2014), and myosin heavy chain proteins (Morita, 2010). These studies have demonstrated that proteins from deep-sea species are functionally less susceptible to increased pressure than those from shallow living species.…”
Section: Introductionmentioning
confidence: 99%
“…intermolecular electrostatic and hydrophobic interactions, dissociating oligomeric and aggregated proteins. The same kind of interactions that maintain the aggregated states also preserve the secondary and tertiary protein structures in their native conformation [5][6][7]. However, more efficient protein hydration followed by disruption of intramolecular bonds and subsequent protein denaturation generally requires pressure higher than 4 and 5 kbar [8].…”
Section: Introductionmentioning
confidence: 99%